Ownership concentration, firm life cycle, and leverage: Evidence from Italian family firms - William Mbanyele (Cogent Economics & Finance, 2020)
We examine the impact of ownership concentration, firm life cycle, and family ownership on leverage using a sample of listed Italian firms. The study findings reveal that family businesses in Italy have high ownership concentration and use less debt than non-family firms. The study results show that there is a nonlinear relationship between ownership concentration and leverage, and between the firm life cycle and leverage. Furthermore, the study contributes to the literature by showing that firm age positively moderates ownership concentration and leverage linkage. Besides we provide evidence that debt and ownership alternate as disciplining devices at different ownership concentration levels and life cycle stages. Our policy contribution encourages regulators to enforce laws that protect minority shareholders in businesses with high ownership concentration.
Keywords: 330; Family firm; financial crisis; GMM; Italy; leverage; life cycle; ownership concentration